2024
DOI: 10.3390/jcm13030835
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation: Effect on Cytokine Profile in Multiple Sclerosis

Maddalena Sparaco,
Simona Bonavita

Abstract: Vitamin D is known for its role in modulating calcium and phosphate homeostasis and is implicated both in bone mineralization and immune system regulation. The immune-modulatory role of vitamin D and its impact on multiple sclerosis (MS) courses are still debated. The aim of this review was to check the effect of vitamin D supplementation on cytokine profile regulation in people with MS. A significant increase in serum concentrations of interleukin (IL)-10 and Transforming growth factor (TGF)-β1 after vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…More recently, several studies have shown a great potential of vitamin D immunomodulatory activities in various non-renal immune diseases, such as vitiligo and multiple sclerosis [104][105][106].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…More recently, several studies have shown a great potential of vitamin D immunomodulatory activities in various non-renal immune diseases, such as vitiligo and multiple sclerosis [104][105][106].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…More recently, several studies have shown a great potential of vitamin D immunomodulatory activities in various non-renal immune diseases, such as vitiligo and multiple sclerosis [111][112][113].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%